Impact of media form on the perceived image of the television news media in the age of media convergence - John W. Cheng; Hitoshi Mitomo (International Telecommunications Society (ITS), 2017)
The aim of this study is to investigate the impact of media form on audiences' perceived image of the television news media. Specifically, it compares the perceived sense of presence between two different media forms –television and smartphone, and examines their effects on the perceived brand personality of a news medium. This study uses NHK –the national public broadcasters– news coverage during the 2016 Kumamoto Earthquake over the air and the Internet as a case study. Using a quantitative approach with data collected from an original survey, it is found that television as a media form provides a stronger sense of presence that smartphone, and also has a stronger influence on the perceived brand personality of a news medium, especially on its perceived competence. That being said, it is also found that smartphone can also exert some influence, in particular on the perceived dynamism and sociability of the medium.
Keywords: 330